An assessment of the training needs in information technology among academic librarians in Metro Manila - Olid, Jocelyn G. (1997)
This study was conducted to find out the training needs in Information Technology (IT) of academic librarians in Metro Manila. The one hundred sixty five (165) professional licensed academic librarians who are members of the 1996 Philippine Librarians Association, Inc. (PLAI) were the respondents of the study. The descriptive method was used with questionnaire as the main data-gathering tool, supplemented by interviews, observation and examination of records.